Competition between two Usutu virus isolates in cell culture and in the common house mosquito Culex pipiens - van Bree, Joyce W. M.; Linthout, Charlotte; van Dijk, Teije; Abbo, Sandra R.; Fros, Jelke J.; Koenraadt, Constantianus J. M.; Pijlman, Gorben P.; Wang, Haidong (Frontiers in Microbiology, 2023)
Usutu virus (USUV) is a mosquito-borne flavivirus of African origin. Over the past decades USUV has spread through Europe causing mass die-offs of multiple bird species. The natural transmission cycle of USUV involves Culex spp. mosquitoes as vector and birds as amplifying host. Next to birds and mosquitoes, USUV has also been isolated from multiple mammalian species, including humans, which are considered dead-end hosts. USUV isolates are phylogenetically classified into an African and European branch, subdivided into eight genetic lineages (Africa 1, 2 and 3, and Europe 1, 2, 3, 4 and 5). Currently, multiple African and European lineages are co-circulating in Europe. Despite the increasing amount of data on the epidemiology and pathogenicity of the different lineages, the effect of co-infection and transmission efficacy of the co-circulating USUV strains remains unclear. Here we report a comparative study between two USUV isolates: a Dutch isolate (USUV-NL, Africa lineage 3) and an Italian isolate (USUV-IT, Europe lineage 2). Upon co-infection, USUV-NL was consistently outcompeted by USUV-IT in mosquito, mammalian, and avian cell lines. In mosquito cells, the fitness advantage of USUV-IT was most prominently observed in comparison to the mammalian or avian cell lines. When Culex pipiens mosquitoes were orally infected the different isolates, no overall differences in vector competence for USUV-IT and USUV-NL were observed. However, during the in vivo co-infection assay it was observed that USUV-NL infectivity and transmission were negatively affected by USUV-IT, but not vice versa.